1999
DOI: 10.1046/j.1472-765x.1999.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of hygiene procedures for prevention of cross-contamination from chicken carcases in the domestic kitchen

Abstract: Thirteen sites in each of 60 domestic kitchens were examined for Salmonella and Campylobacter spp. following the preparation of a chicken for cooking and the application of different hygiene regimes. During food preparation bacteria became widely disseminated to hand and food contact surfaces. Where cleaning was carried out with detergent and hot water using a prescribed routine there was no significant decrease in the frequency of contaminated surfaces. Where hypochlorite was used in addition, a significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
170
3
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(189 citation statements)
references
References 14 publications
11
170
3
5
Order By: Relevance
“…Neste estudo, a amostragem dos panos de limpeza foi realizada somente da superfície, assim, a contaminação real provavelmente seja muito maior. A quantidade de micro-organismos presentes nos panos de limpeza frequentemente é bastante alta, conforme relatado por diversos autores (JOSEPHSON; RUBINO; PEPPER, 1997;COGAN;BLOOMFIELD;HUMPHREY, 1999).…”
Section: Resultsunclassified
“…Neste estudo, a amostragem dos panos de limpeza foi realizada somente da superfície, assim, a contaminação real provavelmente seja muito maior. A quantidade de micro-organismos presentes nos panos de limpeza frequentemente é bastante alta, conforme relatado por diversos autores (JOSEPHSON; RUBINO; PEPPER, 1997;COGAN;BLOOMFIELD;HUMPHREY, 1999).…”
Section: Resultsunclassified
“…Similar studies conducted in several Middle Eastern countries showed supporting results. Wazaify et al, [14], Al-Saeedi et al, [1], Shtayeh et al, [13], Al-Kindi et al, [2], Naja et al, [11] and Al-Asadi et al, [3] have shown that the prevalence of TCAM use amongst diabetic patients in the studied-countries was high, yet the percentages varied. This can be attributed to different definitions of TCAM used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hand hygiene is one of the imperative tools to reduce and prevent surface-to-surface cross-contamination. 13 Cogan et al 14 reported that no Campylobacter jejuni could be recovered from hand-washed cutlery. In contrast, some studies confirm the ineffectiveness of consumer-style hand-washing procedures, 15,16 thus either the hand-washing procedure must be intensified or hand contact with the meat must be prevented.…”
Section: Introductionmentioning
confidence: 99%